Developing a Family Resource: Considerations for Family Member Research Participation. (May 2023) - Polfuss, Michele; Mooney-Doyle, Kim; Keller, Mary; Gralton, Karen S.; Giambra, Barbara; Vance, Ashlee
When individuals participate in health care research, the choice often affects the entire family. Researchers are responsible for protecting participants and minimizing any burdens the research may place on them. Resources to educate potential study participants about these issues from a family perspective are lacking. A family-focused, evidence-based resource was created for individuals and families to prompt discussion prior to their consenting to enrollment in research. The resource includes key relevant questions to consider related to their study participation and was revised based on input from family nurse scientists and a hospital-based family advisory group. This resource raises awareness of the importance of employing a family lens when designing research and during the recruitment and enrollment of participants. Adopting a family lens in health care research will support the participant's ability to make an informed choice regarding participation and may ultimately enhance the experience of participants and their families and study outcomes.